Implementation of the Client-Server System for Ordering Food and Beverages with the Android Platform Using the Waterfall Method (Case Study: Maxx Coffee Prima Ap Kualanamu Store) - Cindy Cintya; R.Fanry Siahaan (Journal of Intelligent Decision Support System (IDSS), 2020)
Today's human needs vary, one of today's human needs is information, which is included in the category of social needs. With technology in the trade sector, it can simplify buying and selling transactions, promoting merchandise, data collection in trading can be easy, and so on. . One of the fields engaged in the trade sector is the Maxx Coffee Prima Store. Maxx Coffee Prima is an authentic Indonesian coffee shop that presents innovative products and the best service designed as comfortable as possible in the form of a full coffee shop where Maxx Coffee Prima presents various types of food And ready-to-serve drinks. The client server will be implemented at the Maxx Coffee Prima Store as a medium for ordering Food and Beverages, by applying the Waterfall method. The waterfall method is a sequential arrangement from planning to testing. So that the system is well structured and can make software quality maintained so that maintenance is easier and as a model for software development approaches. The application of the waterfall on the client server is quite effective because of the well-structured planning using a flow chart.